PRAKTIK PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA BERBASIS KINERJA - Selvi Maramba Hina; Osfred Umbu Djadji (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze human resource training and development in improving the performance of Village-Owned Enterprises (BUMDes) in Umalulu District, East Sumba Regency.Methods: This study uses a qualitative, descriptive approach. Data collection techniques used in this study include field observation, documentation, and in-depth interviews with research informants.Results: The research indicates that human resource training and development initiatives are primarily delivered through direct methods such as outreach, technical guidance, workshops, and simulations. While these approaches have the potential to enhance work performance and efficiency, their impact is not yet optimal. Several limitations persist, including a narrow training focus, varying levels of motivation and enthusiasm, limited relevance of training materials, and budgetary constraints. Therefore, it is essential for village-owned enterprises to implement more structured, strategic, and relevant planning and evaluation processes when analyzing human resource training and development needs. This will support the sustainable improvement of BUMDes' performance. Keywords: Based Performance; Human Resource; Practices; Training and Development